Covalent biofunctionalization of hydrothermal nanocarbons with inner-side-out directed cytomembrane by hydrazone bioconjugation for screening herbal active components - Pinyu Ye; Kaiyi Wang; Menglan Shen; Xinran Yu; Sha Liu; Enxu Liu; Gang Chen; Qiaoyan Zhang; Shan Tao; Lupin Qin; Qiming Zhao (Materials & Design)
The ordered biofunctionalization of hydrothermal nanocarbons played a key role in broadening their advanced biological usages, because the biomacromolecular functions were greatly affected by their direction and biostability. This paper designed novel stable inner-side-out osteoblast membrane bonded hydrothermal magnetic carbonaceous nanospheres (IOM-HMCNs) for screening herbal anti-osteoporotic components targeting to intracellular surface. Bioorthogonal hydrazone chemistry was first used for the directed and covalent immobilization of OMs, in which the cell surface carbohydrates were mildly oxidized into aldose, and linked to hydrazide-functionalized HMCNs through hydrazone bonds. The high stability and inner-side-out OM direction of biocomposite were confirmed by fluorescently labeled assay, immunogold transmission microscopyand the adsorption experiments. IOM-HMCNs successfully identified five specific components, including three novel potential active compounds from Schisandrae chinensis Fructus, which cannot be identified by traditional randomly directed OM bonded HMCNs. Their bioactivity was further validated by osteoblast-based pharmacology and osteoporotic zebrafish tests. Their binding membrane proteins were preliminarily located on insulin-like growth factor receptor 1 and ephrin receptor B4 through molecular docking and western blot analysis. These findings provide a powerful tool for advanced orientable construction of biomaterials through a sustainable route, and also contributed to a comprehensive high-efficiency screening of bioactive compounds from natural products.